Calcinosis cutis in chronic myeloid leukemia - Arun C Inamadar; Anusha Lingaiah; Ajit B Janagond (Wolters Kluwer Medknow Publications, 2022)
Calcinosis cutis is a rare condition of calcium deposition in skin and subcutaneous tissue. Multiple underlying diseases have been implicated for calcification, the pathogenesis of which is poorly understood. We report a case of calcinosis cutis secondary to chronic myeloid leukemia. The case is being reported for its rarity of association.